Electron scattering cross sections from nitrobenzene in the energy range 0.4-1000 eV: The role of dipole interactions in measurements and calculations - Álvarez, Lidia (2020)
FIS2016-80440 LINKA 20085 PD/00193/2012 DP160102787 DP180101655